Reverse Subtitling in the ESP Class to Improve Written Skills in English: A Case Study - Ávila-Cabrera, José Javier (Journal of Audiovisual Translation, 2021)
The improvement of foreign language (L2) skills is of paramount importance in the university context, and a considerable number of students lack linguistic proficiency in their oral and written communication skills. This lack of proficiency needs to be properly addressed and methodologies employed in order to help students improve such skills. There are many cases in which international students, whose cultural background is either European or Asian, need to improve their oral and written production in English as an L2. This paper presents a study conducted at the Universidad Complutense de Madrid throughout the 2017–2018 academic year, in which a number of undergraduate students enrolled in English for Specific Purposes (ESP) used reverse subtitling, from Spanish or Chinese into English, as a learning tool. The main focus of this case study was to enable students to improve their written skills in English through the combined use of Business English and reverse subtitling in accordance with the course content and expectations. A mixed method was used in order to gather and evaluate quantitative and qualitative data. This study therefore aims to bring to the fore the potential of using reverse subtitling in the ESP class. Lay summary Improvement in written and oral skills is a universal task for all university students studying a foreign language. Their goal is to work toward improving their skills in English for Specific Purposes (ESP) by completing the tasks proposed by their lecturers in the subject in which they are enrolled. One of these skills is writing, which is a production skill that requires the lecturer’s supervision. The aim of this paper is to present a study centred on the improvement of written skills in the class of ESP with a majority of students from Spain and a minority from China. The study took place in the 2017–2018 academic year at the Universidad Complutense de Madrid, Spain. Participants submitted compositions in English relating to business and commerce. In addition, they used subtitling as a pedagogical tool to improve their written production in ESP. This practice consisted of transferring the original oral text of a video into subtitles, from Spanish to English (in the case of Spanish speakers) and from Chinese into English (for Chinese speakers). By doing so, we compared quantitative data obtained from the tasks submitted by students, and qualitative data in the form of participant questionnaires in order to observe improvement in their skills. We aim to highlight the pedagogical potential of subtitling for the improvement of written skills in ESP.